TECHNOLOGIES FOR IMPROVING THE MORAL QUALITIES OF CITIZENS OF ANDIRAGOGIC AGE FORMED IN SOCIETY (American Journal of Pedagogical and Educational Research, 2024)
Society is a set of historically determined collaborative activities of people. Everything in society (material and spiritual wealth, the creation of the necessary conditions for human life, etc.) takes place in the course of a certain activity. The development of society has a direct impact on the development and progress of representatives of different social strata. The social sphere of society harmonizes social groups, strata, categories and their lives. Therefore, improving the qualities in the moral education of citizens of the andragogic age formed in society is a prerequisite for a free and prosperous lifestyle.